2019
DOI: 10.1093/mnras/stz1740
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Red Radio Ring’: ionized and molecular gas in a starburst/active galactic nucleus at z ∼ 2.55

Abstract: ABSTRACT We report the detection of the far-infrared (FIR) fine-structure line of singly ionized nitrogen, [N ii] 205 $\mu$m , within the peak epoch of galaxy assembly, from a strongly lensed galaxy, hereafter ‘The Red Radio Ring’; the RRR, at z = 2.55. We combine new observations of the ground-state and mid-J transitions of CO (Jup = 1, 5, 8), and the FIR spectral energy distribution (SED), to explore the multiphase interstellar medium (ISM) properties of the RR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 158 publications
1
10
0
Order By: Relevance
“…Using our measurements of the line intensities, we find an electron density of n e = 290 +90 −70 cm −3 . This elevated electron density could explain the discrepancy found between the [N II] 205µm and L IR -derived SFRs by Harrington et al (2019), since in that work a low electron densityn e ≈ 30 cm −3 -was assumed.…”
Section: Electron Densitymentioning
confidence: 88%
“…Using our measurements of the line intensities, we find an electron density of n e = 290 +90 −70 cm −3 . This elevated electron density could explain the discrepancy found between the [N II] 205µm and L IR -derived SFRs by Harrington et al (2019), since in that work a low electron densityn e ≈ 30 cm −3 -was assumed.…”
Section: Electron Densitymentioning
confidence: 88%
“…All samples cover a similar range in t dep , but the average t dep for the (higher M gas ) high-z samples appear lower. Top right: the r 31 brightness temperature ratio of VLASPECS galaxies (green circles) is similar to that of strongly lensed z∼3 Lyman-break galaxies (red triangles; Riechers et al 2010), z>2 main-sequence galaxies from the PHIBSS survey (gray crosses; Bolatto et al 2015), and z>2 dusty star-forming galaxies (DSFGs; blue squares; compilation from Sharon et al 2016; including data from Danielson et al 2011;Ivison et al 2011;Riechers et al 2011aRiechers et al , 2011bRiechers et al , 2013Thomson et al 2012;Fu et al 2013;Sharon et al 2013Sharon et al , 2015 other DSFGs shown as light gray squares are from Nayyeri et al 2017;Dannerbauer et al 2019;Harrington et al 2019;Leung et al 2019;Sharon et al 2019) and clustered DSFGs (dark gray squares; Bussmann et al 2015;Gómez-Guijarro et al 2019), but ∼2 times higher on average than BzK-selected main-sequence galaxies at z∼1.5 (magenta crosses; Daddi et al 2015). Nearby galaxy samples from the xCOLD GASS survey (Lamperti et al 2020) and two studies of infrared-luminous galaxies (Yao et al 2003;Papadopoulos et al 2012) are shown for comparison.…”
Section: Gas Masses Depletion Times and Line Ratiosmentioning
confidence: 88%
“…We therefore consider them starburst galaxies, without alluding to an assumed SF history. (Harrington et al 2016), (3) (Harrington et al 2019), (4) (Geach et al 2015), ( 5) (Su et al 2017), ( 6) (Geach et al 2018), ( 7) (Rivera et al 2019), ( 8) Kamieneski et al (in prep), ( 9) (Khatri & Gaspari 2016), (10) (Amodeo et al 2018), ( 11) (Cañameras et al 2015), ( 12) (Cañameras et al 2018a), ( 13) (Frye et al 2019), ( 14) (Cañameras et al 2017a), ( 15) (Cañameras et al 2017b), ( 16) (Harrington et al 2018), ( 17) (Cañameras et al 2018c), ( 17) (Bussmann et al 2013)…”
Section: Selectionmentioning
confidence: 99%
“…Focus measurements were repeated roughly 1.5hr after sunset/sunrise and every 3-4hr to correct for thermal deformations of the primary dish and/or secondary mirror. In the same manner presented in Harrington et al (2019), all scans were reduced using GILDAS package 4 , smoothed to ∼ 50 − 150 km s −1 channel resolution, followed by a visual inspection of a baseline-subtracted spectrum and subsequent averaging of the rms-weighted spectrum. We dropped 5-20% of the scans per line due to unstable baselines or noise spikes, which may strongly depend on the specific tuning setup and weather.…”
Section: Gbt Iram 30m and Apex Observationsmentioning
confidence: 99%